(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
Extensive exploration of literatures, stakeholders’ statements, comments, debates and arguments etc from seminars, conferences, fora, meetings, telephone calls, email correspondences, etc are critically reviewed in this paper and are used to argue for improved ways and methods of architetural design education. Although there are similarities in the curriculas of training architects all over the world, but educators go about it in their own convenient and suitable ways and styles. Collaboration of academic and practicing architects’ participation in teaching of the arch-design studio and integrated course work with other disciplines are not new in training of architects, this review goes further to argue for a selection criteria and more integration especially of related professionals in the building industry in teaching the arch-design studio. Training to think globally and act locally (adaptable) hence sustainability and creativity are taken as the central themes for effective delivery of arch-design educat on. The topic is very relevant and timely as arch-educators and other stakeholders are of the opinion that something has to be done to improve the ways and methods of training architects, especially the teaching of the arch-design studio. The paper uses the theoritical under-pinnings of collaboration, integration and adaptability to argue for or against the ways and methods of teaching the arch-design studio and recommends the participants that will be making meaniful and positive contributions to the effective teaching of the arch-design studio. That is more of team work (integration and collaboration) but based on selection process of who should participate in the teaching and that is adaptable to the people and the environment.